2017
DOI: 10.14191/atmos.2017.27.1.041
|View full text |Cite
|
Sign up to set email alerts
|

Potential Source of PM10, PM2.5, and OC and EC in Seoul During Spring 2016

Abstract: Organic carbon (OC) and elemental carbon (EC) in PM 2.5 were measured using Sunset OC/EC Field Analyzer at Seoul Hwangsa Monitoring Center from March to April, 2016. The mean concentrations of OC and EC during the entire period were 4.4 ± 2.0 μgC m −3 and 1.4 ± 0.6 μgC m −3 , respectively. OC/EC ratio was 3.4 ± 1.0. The average concentrations of PM 10 and PM 2.5 were 57.4 ± 25.9 and 39.7 ± 19.8 μg m , respectively, which were detected by an optical particle counter. The OC and EC peaks were observed in the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Various results and indicators in a study of fine dust pollution from 2011 to 2015 were similar to the results of our study based on the economic indicators of the Seoul metropolitan area [14]. Other studies have found that monthly changes in the concentration of fine dust are related to the seasons; the concentrations increased in November, peaked in February, and then decreased gradually and reached their lowest levels in August and September [15,16].…”
Section: Discussionsupporting
confidence: 88%
“…Various results and indicators in a study of fine dust pollution from 2011 to 2015 were similar to the results of our study based on the economic indicators of the Seoul metropolitan area [14]. Other studies have found that monthly changes in the concentration of fine dust are related to the seasons; the concentrations increased in November, peaked in February, and then decreased gradually and reached their lowest levels in August and September [15,16].…”
Section: Discussionsupporting
confidence: 88%
“…Various results and indicators in a study of fine dust pollution from 2011 to 2015 were similar to the results of our study based on the economic indicators of the Seoul metropolitan area [14]. Other studies have found that monthly changes in the concentration of fine dust were related to the seasons; the concentrations increased beginning in November, peaked in February, then decreased gradually and reached the lowest level in August and September [15,16].…”
Section: Discussionsupporting
confidence: 88%
“…Recently, there have been many studies to characterize chemical species of PM 2.5 nationwide in Korea such as a study of chemical characteristics of PM 2.5 in Seoul in 2019 (Um et al, 2020), a study of the origins and distributions of atmospheric ammonia in Jeonju during 2019-2020 (Park et al, 2020), a study on the characteristics of PM 2.5 chemical compositions and high-concentration episodes from 2013 to 2016 in Jeju (Kim et al, 2020), a study on PM 2.5 and its chemical compositions from 2017 to 2018 in Jeonju ( Jo et al, 2018), estimation of emission source contribution of OC and EC in the spring of 2016 in Seoul (Ham et al, 2017), and a study on the distribution of heavy metals during 2013 and 2014 in Gyeonggido (Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%